2016
DOI: 10.5812/ircmj.34695
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Application of Sweet Almond Oil on Reducing Uremic Pruritus in Hemodialysis Patients: A Randomized Clinical Trial Study

Abstract: Background: While the application of anti-pruritus medications may be useful for hemodialysis (HD) patients, they are at risk of drug toxicity because of their renal inability to eliminate drug metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…In addition, sweet almond is an oral substance that is not allergen nor toxic for skin (18); its effects on itchyQoL may be useful. Results of other studies showed that topical application of sweet almond oil significantly reduced the uremic pruritus in patients undergoing hemodialysis, without any specific complications (19). To the authors' best knowledge, no similar study was available in the international scientific databases; hence, the current study aimed at examining the effect of topical application of sweet almond oil on itchyQoL in patients with uremic pruritus.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, sweet almond is an oral substance that is not allergen nor toxic for skin (18); its effects on itchyQoL may be useful. Results of other studies showed that topical application of sweet almond oil significantly reduced the uremic pruritus in patients undergoing hemodialysis, without any specific complications (19). To the authors' best knowledge, no similar study was available in the international scientific databases; hence, the current study aimed at examining the effect of topical application of sweet almond oil on itchyQoL in patients with uremic pruritus.…”
Section: Introductionmentioning
confidence: 93%
“…Respondent reported a decrease in itching (pruritus) after giving turmeric oil aromatherapy for 2 weeks, and became more relaxed, and slept more tightly at night. This is supported by research conducted by (Afrasiabifar et al, 2016) which proves that the administration of sweet almond oil aromatherapy can significantly reduce the symptoms of uremic pruritus after giving topically once a day for 2 weeks. It can be concluded that the administration of turmeric oil aromatherapy, is effective in reducing uremic pruritus.…”
Section: Discussionmentioning
confidence: 72%
“…Turmeric aromatherapy has good smell that is familiar and loved by Indonesian people. Researcher suspect that aromatherapy turmeric oil can reduce uremic pruritus symptoms by alleviating the inflammatory process that play a role in releasing pruritogen (Abdelghfar, Elsebae, Elhadry, & Hassan, 2017;Afrasiabifar, Mehri, & Hosseini, 2016;Curcani & Tan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, arachidonic and linoleic acids play a protective role in the skin and their deficiency in patients undergoing HD may lead to dermatological complaints such as pruritus. (Afrasiabifar, Mehri and Hosseini, 2017) In justifying the effectiveness of sweet almond oil on the relief of uremic pruritus, it can be said that sweet almond contains essential fatty acids such as linoleic acid that have been shown to be effective in relieving pruritus.…”
Section: Effectiveness Of Sweet Almond Oil For Treating Uremic Pruritusmentioning
confidence: 99%